2022
DOI: 10.46456/jisdep.v3i2.308
|View full text |Cite
|
Sign up to set email alerts
|

Does the Pandemic Affect Unemployment Rate in East Java? (A Study of Pre and Post COVID-19 Pandemic in 2016 to 2021)

Abstract: This paper aimed to identify the problems caused by labor policy in the 2016 – 2020 period in the province of East Java. This study can be a response to the employment problems being experienced by the people of East Java before and after the COVID-19 pandemic in Indonesia. Thus, it is necessary to conduct further studies to provide relevant recommendations regarding appropriate labor policies. The method used in this research was the descriptive method and analytical techniques using the unemployment rate, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Although fluctuating, the unemployment rate went up in 2021 to 5.42% before dropping to 5.26% in 2022. Coupled with the change in TPAK in the same year, from 72.32% in 2021 to 72.00% in 2022 [1] the unemployment problem in Banyuwangi shows its complexity. One particular challenge for the Vocational High School graduates is the lack of experience, skills and insights that make them hesitant to start their own business.…”
Section: Introductionmentioning
confidence: 99%
“…Although fluctuating, the unemployment rate went up in 2021 to 5.42% before dropping to 5.26% in 2022. Coupled with the change in TPAK in the same year, from 72.32% in 2021 to 72.00% in 2022 [1] the unemployment problem in Banyuwangi shows its complexity. One particular challenge for the Vocational High School graduates is the lack of experience, skills and insights that make them hesitant to start their own business.…”
Section: Introductionmentioning
confidence: 99%
“…BPS reported that the number of unemployed in the first quarter of 2020 reached 8.75 million and increased in the first quarter of 2021 to 9.77 million unemployed. Apart from having an impact on increasing the number of unemployed, this pandemic also has an impact on reducing working hours and income (Romadhona, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(Saputra et al, 2021) The basic considerations based on studies from the Ministry of National Development Planning/Bappenas in determining the location for relocating the national capital to East Bappenas in his study stated that the transfer of IKN would have a positive impact on the national economy with a predicted increase in GRDP of 0.1%. (Romadhona, 2022) Bappenas states that the increase in GRDP comes from the utilization of potential resources, such as land clearing for productive infrastructure needs and job opportunities for skilled human resources which have not been utilized so far. Bappenas specifically estimates that there will be an increase in labor wages for the surrounding area as reflected in an increase in the price of labor of 1.37%, the transfer of IKN is predicted to increase national economic growth with a controlled inflation rate.…”
Section: Introductionmentioning
confidence: 99%